A comparison of outcomes for children and youth in foster and residential group care across agencies. (January 2018) - Portwood, Sharon G.; Boyd, Suzanne A.; Nelson, Ellissa Brooks; Murdock, Tamera B.; Hamilton, Jessica; Miller, Angela D.
Abstract: Working collaboratively with two state associations and their member (nonprofit) agencies providing out-of-home care to children and youth, University researchers conducted a multi-site project to examine whether there were any differences in individual child-level outcomes between children placed in residential group care and those placed in foster. The study employed a quasi-experimental repeated measures design, with data collected at a minimum of two intervals (at intake and 3-month follow-up) and at subsequent intervals of 6 and 12 months for children remaining in care. Samples for analyses were drawn from 1082 youth in either residential group care ( n  = 903) or foster care ( n  = 179), in one of 37 agency sites across two southeastern states, who participated in a broader evaluation project. The average ages of participating youth in residential and foster care were 13.97 (SD = 2.43) and 13.65 (SD = 2.73), respectively. Based on his or her score on the Children's Global Assessment Scale (CGAS) at intake, each participant was also assigned to the low functioning group ( n  = 526; 53.1%), the borderline group ( n  = 232; 23.4%), or the high functioning group ( n  = 232; 23.4%). Analyses confirmed that youth in foster care tended to have higher levels of general functioning at baseline than did youth placed in group care. However, the degree to which youth progressed in care on measures of general functioning and mental and behavioral health problems did not differ based on placement setting; youth in residential group care settings progressed at the same rate as youth in community-based settings, regardless of their level of functioning at intake. The only exception to this pattern was in regard to anxiety; there was an observable, but non-significant trend of youth in foster care reporting decreases in anxiety levels, while those in group care reported increased anxiety. Highlights: Youth placed in foster care tended to have higher levels of functioning at intake than did youth placed in group care. Youths' progression in care on general functioning and behavioral/mental health problems did not differ based on placement. While non-significant, trends of increasing anxiety among children in residential care merit further investigation. The findings support residential group care as part of an effective continuum of care for children and youth.